A new approach for selection of transgressive segregants in F3 populations based on selection index and anthocyanin content in cayenne pepper - Anshori, Muhammad Fuad; Musa, Yunus; Dungga, Novaty Eny; Widiayani, Nuniek; Arifin, Arfina Sukmawati; Masniawati, Andi; Firmansyah, Firmansyah; Farid, Muh; Dirpan, Andi; Amas, Azmi Nur Karimah (Frontiers in Sustainable Food Systems, 2024)
The development of cayenne pepper varieties can be optimized by multiple crossings, transgressive segregant selection based on the selection index, and identification of potential anthocyanins. The study objectives were (1) to develop a transgressive segregation index, and (2) to select transgressive segregation cayenne peppers with high productivity and anthocyanins from F3 multiple cross-generation. The study conducted two experiments at the experimental field, Hasanuddin University, from November 2022 to November 2023. The first experiment implemented an augmented design with a randomized complete block design (RCBD) as an environmental design. The genotypes as treatment consisted of two types: 110 lines of cayenne pepper were not repeated, and the four older chili varieties as controls were repeated in each block. All genotypes were categorized and divided into five blocks. The second experiment was the validation of the first trial. There were 13 genotypes tested with RCBD design one factor and repeated three times. Based on the study, developing a semi-objective-based selection index with canopy width, fruit weight, and yield was an innovative and effective approach in selecting F3 transgressive segregants of cayenne pepper. High-yielding transgressive lines were identified as G3-2-7-3, G2.6.9-10, G5-12-1-8, and G4.5.2-12. The G3-2-7-3 line was suggested due to its high yield potential and anthocyanin content. However, the anthocyanin content must be examined more deeply, such as using an omics approach. Nevertheless, these lines are still recommended to be continued in yield testing or crossing to produce hybrid lines that have high yield potential and anthocyanin content.